2016
DOI: 10.1080/09712119.2016.1150846
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of chemically amended litter on litter quality and broiler performance in winter

Abstract: The experiment was conducted to study the efficacy of different types of litter amendments on litter quality and broiler performance during winter (December-January). A total number of 180, day-old (Vencobb) broiler chicks were randomly assigned to three equal groups. One bearing control group and other two comprise litter amendments with alum (ATL) and sodium bisulphate (SBTL) treatment groups, each having 60 birds in three replications of 20 numbers for 6 weeks. The findings of the study revealed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
(18 reference statements)
5
11
0
3
Order By: Relevance
“…The beneficial effects of liquid AlCl 3 on growth performance in broiler chickens were previously reported by Choi and Moore (2008b). Sahoo et al (2017) observed that during winter, the addition of alum and sodium bisulfate to litter increased broiler growth performance. The discrepancies between the results of these previous studies and the present study suggest that other factors such as sex, litter additive characteristics and poultry species could influence the outcomes.…”
Section: Resultsmentioning
confidence: 54%
“…The beneficial effects of liquid AlCl 3 on growth performance in broiler chickens were previously reported by Choi and Moore (2008b). Sahoo et al (2017) observed that during winter, the addition of alum and sodium bisulfate to litter increased broiler growth performance. The discrepancies between the results of these previous studies and the present study suggest that other factors such as sex, litter additive characteristics and poultry species could influence the outcomes.…”
Section: Resultsmentioning
confidence: 54%
“…Of the 23 trials that measured footpad lesions as a binary outcome, one trial had all zero cells (i.e. no birds had footpad lesions) (Sahoo et al, 2017) and all birds were positive for the outcome in another trial (Vargas-Galicia et al, 2017); relative effect sizes could not be calculated in either case. There were five trials from four publications in which the intervention arms collapsed into the same intervention based on our treatment map (Petek et al, 2010;Gholap et al, 2012;Avdalovic et al, 2017;Shepherd et al, 2017).…”
Section: Results Of Individual Studies Included In the Networkmentioning
confidence: 99%
“…Sahoo et al . [ 48 ] found that treating litter with SBTL was able to reduce Eimeria oocyst count to a little extent compared to ATL and control, although, of the numerical values, differences between the two amendments were statistically non-significant.…”
Section: Discussionmentioning
confidence: 99%